The Impact of Space Radiation on Brains of Future Martian and Lunar Explorers - Yuncong Li; Jingnan Guo; Salman Khaksarighiri; Mikhail Igorevich Dobynde; Jian Zhang; Bailiang Liu; Robert F. Wimmer‐Schweingruber (Space Weather)
Abstract Astronauts will be facing many risks when they are away from Earth's environment, among which radiation is one of the most vital and troublesome issues. Space radiation exposure from energetic particles of Solar Energetic Particles (SEPs) and Galactic Cosmic Rays (GCRs) can adversely impact the Central Nervous System (CNS) by inducing acute (i.e., mission critical) and chronic (i.e., post‐mission) effects, respectively. Recently, Brain Response Functions (BRFs) based on a realistic brain structure have been developed to model cosmic‐ray induced dose in the brain (Khaksarighiri et al., 2020, https://doi.org/10.1016/j.lssr.2020.07.003). In this study, to quantify the radiation induced dose and evaluate the radiation risk to the CNS of the astronauts on the surface of Mars and Moon and in deep space, we use GCR/SEP spectral models together with Mars/Moon radiation transport codes to obtain the radiation field to which astronauts are exposed, and derive the absorbed dose in the brain with BRFs. Our calculations show that GCR induced absorbed dose per month in the brain does not reach the 30‐day limit for CNS (500 mGy) as defined by NASA on either Martian or lunar surface. Based on the spectra and frequency of historical extreme SEP events recorded at Earth as ground‐level enhancement events over past five solar cycles, our results suggest that the CNS of astronauts will be generally “safe” on the Martian surface, but those on the lunar surface or in deep space may face radiation risks in their CNS if not well shielded during such extreme events.